Pertunjukan Sere Api Di Desa Gattareng Kecamatan Pujananting Kabupaten Barru (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to (i) analyze the process of fire performance in Gattareng Village, Pujananting District, Barru Regency. (ii) analyze the dialectic of Bugis and Islamic culture in the Sere api performance in Gattareng Village, Pujananting District, Barru Regency. (iii) analyze the cultural changes contained in the fire sere performance in Gattareng Village, Pujananting District, Barru Regency. This type of research is a qualitative research by presenting data in the form of narrative-descriptive, which aims to provide an in-depth understanding related to the Sere api Performance in Gattareng Village, Pujananting District, Barru Regency by interviewing 7 informants. The data collection techniques in this study are observation, interviews and documentation. As well as using the source triangulation data validity technique. The results of the study show that (i) the performance process which is divided into three main stages of preparation, implementation, and closing shows the depth of cultural meaning and spirituality of the community. The preparatory stage reflects gratitude and well-being through young rice harvests and purification rituals. The performance of the performance, which is characterized by the sound of mortars and a procession of fireworks, depicts the courage and inner strength of the participants, as well as the spiritual transformation that occurs during the ritual. The end of the performance, which is marked by the extinguishing of the fire and the harmony of movement, signifies the completion of the ritual in a sacred way. (ii) This tradition is not just a physical performance, but a ritual that combines traditional values (pangngadereng) with Islamic teachings in a complementary way. No conflict was found between the two; On the contrary, Islamic values provide a spiritual and moral framework for the implementation of rituals, while Bugis culture provides the structure and form of expression of the rite. (iii) The Sere api performance has not undergone significant changes from year to year. The procession is still carried out according to the traditional pattern as a form of respect for the ancestors and a symbol of the community's cultural identity. However, there is flexibility in terms of the time and location of the performance.